Quantification of Bioactive Metabolites Derived from Cell-Free Supernatant of Pediococcus acidilactici and Screening their Protective Properties in Frankfurters - Incili, Gokhan Kursad; Akgol, Muzeyyen; Karatepe, Pinar; Uner, Sefa; Tekin, Ali; Kanmaz, Hilal; Hayaloglu, Ali Adnan (Springer, 2025)
The specific aims of the current study were to determine and quantify the bioactive compounds derived from the cell-free supernatant (CFS) of Pediococcus acidilactici and screen their protective effect in frankfurters by applying an edible coating. This was achieved by immersing the peeled frankfurters in the CFS (CFS: 50% and 100%) alone or in combination with chitosan (CH: 0.5% and 1%) solutions for 3 min. Untreated frankfurter samples (control) exceeded the maximum acceptable total viable count limit (7.0 log(10)) on the 14th day, whereas samples treated with 100% CFS + 1% chitosan reached the limit on day 28 during refrigerated storage (P < 0.05). This treatment provided a 14-day extension to the shelf life of frankfurters without causing any significant changes in color and sensory attributes (P > 0.05). Additionally, this treatment inhibited oxidation in the frankfurters, leading to no significant changes in TBA and TVB-N within this group during storage (P > 0.05). This protective effect was mainly attributed to the wide variety of bioactive compounds identified in the CFS, including a total of 5 organic acids, 20 free amino acids, 11 free fatty acids, 77 volatiles, and 10 polyphenols. Due to these bioactive compounds, CFS exhibited a strong radical scavenging capacity (DPPH: 435.08 TEAC/L, ABTS: 75.01 +/- 0.14 mg TEAC/L; FRAP: 1.30 +/- 0.03 mM FE/L) and antimicrobial activity against microorganisms primarily responsible for the spoilage of frankfurters. In conclusion, the results indicate that the CFS contains high levels of bioactive metabolites, and an edible chitosan coating impregnated with CFS can be utilized to extend the shelf life of frankfurters through its antimicrobial effects and oxidation stabilization.
Keywords: Cell-free supernatant; Bioactive metabolites; Edible coating; Frankfurter; Shelf-life, Chitosan